'Noticing' in health professions education: Time to pay attention?. Issue 4 (29th November 2022) - Clement, Tim; Bolton, Joanne; Griffiths, Leonie; Cracknell, Carolyn; Molloy, Elizabeth
Abstract: Background: Health professions education teaches students to notice particular things, but has given little attention to teaching 'noticing' as a form of personal inquiry. The former is self‐evidently important, as it develops a way of seeing and behaving that is uniquely relevant to each health profession. Despite this emphasis, health professionals may fail to notice 'warning signs' in patients, be unaware of their own biases or develop unrecognised habits that have moved away from accepted standards. It has been suggested that such 'not noticing' is currently endemic. Approach: We situate our exploration of noticing in the mathematics and science education literature and John Mason's treatise on 'The discipline of noticing', differentiating between the observations that people make as they go about their lives ('ordinary' noticing), the specialised noticing that underpins professional expertise (Professional Noticing) and practices that can enhance the capacity to notice and to learn from experience (Intentional Noticing). We make the case for teaching health professions students about these conceptualisations of noticing, being able to notice with all our senses, and learning about the practices of Intentional Noticing in particular, which we suggest will have utility across health professional careers and personal lives. Implications: We acknowledge the difficulties in transferring heterogenous finding from one field to another but suggest that there are gains to be made in applying these noticing concepts to health professions education. We tentatively propose some strategies and activities for developing Professional Noticing and the practices of Intentional Noticing and link them to a new module that we are piloting with health professions students. As well as aiding health professionals sharpen their noticing abilities, reinvigorate their practice and interrogate assumptions that underpin health care, we suggest that ideas about 'noticing' may also help educators and researchers in the health professions reimagine their work. Abstract : 'Not noticing' can have profound consequences for patients. In this paper, the authors explore how concepts of noticing that have been utilized in teacher education can be applied in health professions education.